DAKWAH ISLAM DAN KEHARUSAN PEMBENTUKAN NEGARA - Komaruddin Komaruddin (Wardah, 2011)
Discourse whether or not propaganda (struggle) Muslims are embodied in a form of Islamic state into a debate that never ends and always seemed to find momentum. History proves that the progress achieved and also Muslims in it the spirit of Islam as a missionary spirit, reached after the Muslims succeeded in building a nation (daulah) is characterized by the establishment of the first Islamic government in Medina as his first capital. Instead setback rule (caliphate) Islam is also correlated with the decline of Islam. However, in the present context to impose the Caliphate as the only solution may be counter-productive to the mission itself. Propagation of Islam must start with individuals forming a whole.